For the Grater, Good: The Value of Informal Experiments for Understanding Bipolar Flaking and Manioc Grater Teeth - John C. Whittaker; Mary Jane Berman (EXARC Journal)
Informal experiential experimentation is often helpful for understanding a technology and raising interpretive questions and testable hypotheses. Here, a simple experiment in manufacturing microlithic flakes by bipolar percussion and using them as teeth in a wooden grater, helped us understand archaeological evidence of such teeth and the ‘manioc complex’ on San Salvador, Bahamas. A simple technology may not be unskilled, and the resulting products may appear crude yet function effectively. The lack of evidence of small stone tools may be the result of taphonomic or recovery processes, but if grater tooth manufacture was common at excavated sites, more evidence should survive.